Making of Diagnostic Assessment in the Wizer.Me-Based Problem-Based Learning (PBL) Model to Measure Students' Critical Thinking Skills - ismi gustia (Physics Learning and Education, 2025)
This study aims to determine the level of validity and practicality of diagnostic assessments. The ADDIE (Analysis, Design, Development, Implementation, Evaluation) design model was used in this study. The data sources were obtained from the validation results of physics lecturers at the Faculty of Mathematics and Natural Sciences, UNP. The practicality data sources were obtained from teachers and students of class XII F1 at SMA Negeri 2 Batusangkar. The data analysis method for product validation used Aiken's V, and practicality used the percentage technique. The validation test results, which were assessed based on content feasibility, language use, presentation feasibility, and assessment graphics, were categorized as high at 0.87. With product practicality criteria that included ease of use, attractiveness, and efficiency for teachers and students, the results were 91.3% and 73.08%, respectively, which were categorized as very practical and practical. Therefore, it can be concluded that this PBL diagnostic assessment product on temperature and heat for grade XI high school can be used to evaluate the physics learning process.